(untitled) (The Gaze: Journal of Tourism and Hospitality, 2020)
The relationship in the tourism supply chain management could in turn be a catalyst towards development of the sectoring the continent. Th is paper explore areas of integration in the tourism supply chain among Regional Economic Communities (REC’s) through contextualization of a comparative advantage to increase the share of the tourism business in Africa as a catalyst to development in the African continent. This paper adopted the text analysis that is used in social science research and involves “drawing inferences from a comparative advantage theory”. In this case, large volumes of contents are analysed. Themes that emerged revealed that a well-managed tourism supply chain in the country and in the Regional Economic Communities (REC’s) could stimulate the infrastructural development and preserve natural and historical heritage. TSCM has the ability to support the society. There is a dire need to liberalize air flight and visa regimes to benefit from the share of tourism in the REC’s in the African continent. The implication is that tourism distribution can be achieved through the recognition of the nature of strategic coordination between partners in the RECS and can also improve the performance of the tourism sector in the continent. For companies that are involved in the effective supply chain, they could benefit from coordination and communication through the distribution channels that support the core service or product.